Substitution-based approach for linguistic steganography using antonym - Mansor, Fawwaz Zamir (2017)
Steganography has been a part of information technology security since a long time ago. The study of steganography is getting attention from researchers because it helps to strengthen the security in protecting content message during this era of Information Technology. In this study, the use of substitution-based approach for linguistic steganography using antonym is proposed where it is expected to be an alternative to the existing substitution approach that using synonym. This approach still hides the message as existing approach but its will change the semantic of the stego text from cover text. A tool has been developed to test the proposed approach and it has been verified and validated. This proposed approach has been verified based on its character length stego text towards the cover text, bit size types of the secret text towards the stego text and bit size types of the cover text towards the stego text. It has also been validated using four parameters, which are precision, recall, f-measure, and accuracy. All the results showed that the proposed approach was very effective and comparable to the existing synonym-based substitution approach.